Backlash Against International Courts in West, East and Southern Africa. (2015) - Helfer, Laurence R.
Abstract : In a working paper based on extensive field research and interviews, Karen Alter, James Gathii, and I analyze three recent backlash attempts against sub-regional courts in East, West, and Southern Africa. Our paper analyzes credible proposals by African governments to restrict the jurisdiction of these courts in response to politically embarrassing rulings. These events are not widely known, and they are at odds with the prevailing view that it is difficult to sanction international judges.